Insulin-like growth factors and their carrier proteins in kidneys of rats with experimental diabetes, malignant tumor, and their combination - E. M. Frantsiyants; V. A. Bandovkina; I. V. Kaplieva; E. I. Surikova; I. V. Neskubina; Yu. A. Pogorelova; L. K. Trepitaki; N. D. Cheryarina; I. M. Kotieva; M. I. Morozova (Бюллетень сибирской медицины, 2022)
Persistent hyperglycemia resulting from diabetes mellitus causes microvascular lesions and long-term diabetic complications, such as nephropathy.The aim of the study was to analyze the levels of insulin-like growth factors (IGFs), their carrier proteins (IGFBP), and markers of kidney tissue damage (IL-18, L-FABP, cystatin C, NGAL, and KIM-1) in male rats with diabetes mellitus, tumor growth, and their combination.Materials and methods. The study included white outbred male rats (n = 32) weighing 180–220 g. The animals were divided into four groups (n = 8 each): group 1 – intact animals; controls (2) – animals with diabetes mellitus; controls (3) – animals with Guerin carcinoma; experimental group (4) – animals with Guerin carcinoma against the background of diabetes mellitus. Levels of IGF-1, IGF-2, IGFBP-1, IGFBP-2 and markers of acute kidney injury (IL-18, L-FABP, cystatin С, NGAL, and KIM-1) were determined in the kidney homogenates using enzyme-linked immunosorbent assay.Results. Increased levels of acute kidney injury markers were found in the kidneys of male rats with diabetes mellitus alone and in combination with Guerin carcinoma. In the animals with diabetes mellitus, the levels of IGF-1, IGFBP-1, and IGFBP-2 were decreased on average by 1.3 times, and the level of IGF-2 was increased by 2.1 times compared with the values in the intact male rats. The elevation of IGF-2 / IGF-1 on average by 2.8 times indicated increasing hypoglycemia in the kidney tissue of the animals with diabetes mellitus and in the experimental group with diabetes mellitus and Guerin carcinoma. In the kidney tissues of the rats with Guerin carcinoma, IGF-1 and IGF-2 were elevated on average by 1.5 times, and IGFBP-2 was decreased by 1.7 times. In the animals with malignant tumors growing against the background of diabetes mellitus, IGF-2 and IGFBP-1 were increased by 2.3 and 1.7 times, respectively, and the levels of IGF-1 and IGFBP-2 were similar to those in the intact animals.Conclusion. The study demonstrated abnormalities in the metabolic profile of the kidneys in male rats with experimental diabetes mellitus, Guerin carcinoma, and their combination.